A history of modern political thought major political thinkers from Hobbes to Marx - Hampsher-Monk, Iain. (Oxford Cambridge, 1992)
Iain Hampsher-Monk?s lucid and accessible history of modern political thought is the introduction which many have been waiting for, providing a thorough guide to the ideas and writings of major political thinkers from Hobbes to Marx (including a full account of The Federalist papers).
Includes bibliographical references (p. [563]-592) and index.
Keywords: Political science--History.